Effect of counterion on the catalytic activity of NHC-gold(I) in A3 coupling reactions - Marco Sirignano; Chiara Costabile; Annaluisa Mariconda; Pasquale Longo (Results in Chemistry, 2023)
Synthetic A3-coupling represents an efficient and environmentally convenient procedure for the production of propargylamines, relevant intermediates for the preparation of pharmacologically active substances. Gold(I) complexes of general formula NHC-Au-X have been synthesized, characterized, and tested in the A3-coupling reaction of benzaldehyde, piperidine and phenylacetylene on varying the anionic fragment X as halogenide (Cl, Br, I), acetate (OAc), hexafluorophosphate (PF6) or phenylacetylide (-C≡CPh), with 5-dichloro[N-methyl, N’(2-hydroxy-2-phenyl)ethyl imidazole-2-ylidene as NHC ligand. The kinetic profiles were interpreted with DFT (Density Functional Theory) studies on bond dissociation energies (BDE) of the counterion as well as on the relative stability of the neutral NHC-Au-X complexes with respect to their ionic forms [Au(NHC)2]+[AuX2]−.